RELIGIOUS OPENNESS AND HUMANE VALUES: A CALL FOR UNITY IN A MULTIFACETED WORLD - Husna Amin; Jemmy; Indarta Priyana; Asep Khomeiny Farhan; Samud (ADISAM Publisher, 2024)
Religious openness emerges as a beacon of hope and a vital call for unity in a world characterized by unprecedented diversity and interconnectedness. This abstract explores the profound importance of religious openness in fostering humane values and harmonious coexistence within multifaceted societies. Religious openness encapsulates embracing and respecting diverse religious beliefs, practices, and identities while upholding the principles of religious freedom and tolerance. It is a cornerstone of social cohesion and peace, particularly in regions like Indonesia, where religious diversity is a defining characteristic. This paper delves into the historical context of religious pluralism in Indonesia, highlighting the nation's rich tapestry of beliefs and practices while acknowledging the challenges of religious extremism. It underscores the pivotal role of education, youth engagement, and media literacy in shaping attitudes and fostering religious openness. Moreover, the abstract emphasizes the implications for policy and practice, advocating for educational reforms, interfaith dialogue, and international collaboration. It also underscores the need for further research to assess these initiatives' long-term impact and draw valuable lessons from comparative analyses with other nations facing similar challenges. In conclusion, this abstract underscores that religious openness is not a mere aspiration but a moral imperative in a multifaceted world. It calls upon individuals, communities, and nations to embrace religious diversity, promote humane values, and work towards unity, recognizing that a more inclusive and harmonious future is within reach through religious openness.